Atomically accurate structural tailoring of thiacalix[4]arene-protected copper(ii)-based metallamacrocycles. Issue 17 (21st April 2023) - Mu, Wen-Lei; Wu, Linlin; Yu, Wei-Dong; Yi, Xiao-Yi; Yan, Jun; Liu, Chao
Abstract : Here we have achieved accurate ligand tailoring at specific sites on calixarene-protected Cu(ii )-based metallamacrocycles. Abstract : Accurate manipulation of ligands at specific sites in robust clusters is attractive but difficult, especially for those ligands that coordinate in intricate binding patterns. By linking the shuttlecock-like Cu4 (μ4 -Cl)TC4A motif and the phenylphosphate (PhPO3 2− ) ligand, we elaborately design and synthesize two Cu(ii )-thiacalix[4]arene metallamacrocycles (MMCs), namely Cu12 L3 and Cu16 L4, which have regular triangular and quadrilateral topologies, respectively. While keeping the core intact, the Cl − and PhPO3 2− in those two MMCs, which coordinated in a μ4 -bridging fashion, can be accurately substituted with salicylate ligands. Theoretical calculations have been carried out to reveal the effect of ligand tailoring on the electronic structure of clusters. Structural regulation can affect the catalytic activity of these clusters, which has been verified by using the clusters as catalysts for selective sulfide oxidation.